O'Reilly. "Racial Matters" - The FBI's Secret File on Black American, 1960-1972 - Jirran, Raymond (Teaching History: A Journal of Methods, 1991)
O'Reilly legitimates the dream of Martin Luther King, Jr., for America. "No better gauge of the moral state of the United States' domestic policy exists than the history of the federal government's relationship with its most disadvantaged citizens." O'Reilly has no use for the dilemma imposed by the FBI. "Black America's FBI story is also America's story, but it evokes a sense of shame, not celebration." Therein lies a problem.